1998
DOI: 10.1111/j.1945-5100.1998.tb01330.x
|View full text |Cite
|
Sign up to set email alerts
|

The Guenie and Gao chondrites from Burkina Faso: Probably a single shower of stones

Abstract: Abstract-Two H4-5 meteorite showers have been reported to have fallen at one month intervals in the Guenie-Gao area, but eyewitness accounts are imprecise. Though subtle mineralogical differences are found between stones with different 21Ne content, these differences are insufficient to confirm that two meteorite falls had occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Gao–Guenie has been reported as microbrecciated (Michel‐Levy ; Bourot‐Denise et al. ); Michel‐Levy () further reported the presence of an unusual dark clast in a sample, which could suggest heterogeneity on the scale of the samples used for the magnetic susceptibility measurements. More recently, Gao–Guenie has been described as an impact melt breccia (Schmeider et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao–Guenie has been reported as microbrecciated (Michel‐Levy ; Bourot‐Denise et al. ); Michel‐Levy () further reported the presence of an unusual dark clast in a sample, which could suggest heterogeneity on the scale of the samples used for the magnetic susceptibility measurements. More recently, Gao–Guenie has been described as an impact melt breccia (Schmeider et al.…”
Section: Resultsmentioning
confidence: 99%
“…Originally described as two separate falls (Gao and Guenie, respectively), later analysis confirmed that they were indistinguishable from each other, and were thus reclassified as a single meteorite (Bourot‐Denise et al. ). Gao–Guenie has been reported as microbrecciated (Michel‐Levy ; Bourot‐Denise et al.…”
Section: Resultsmentioning
confidence: 99%
“…At various times, it has been suggested in the literature that two and possibly three meteorites fell within relatively short order of each other in the same region of Gao and Guenie (Walton, 1995;Otto et al, 1996). It is now reasonably clear, however, that all of the H5 chondrite meteorites collected in the Gao-Guenie strewn-field are from just one shower of stones (Bourbot-Denise et al, 1998). This being said, in addition to the H5 Gao-Guenie chondrite under study here carbonaceous chondrite meteorite finds have been collected in the same area.…”
Section: Introductionmentioning
confidence: 92%
“…(Grady, 2000). The meteorite suffered significant fragmentation during its atmospheric flight, as indicated by the presence of secondary ablation crust on many of the recovered fragments, and several hundreds of kilograms of small stones have been recovered from an extensive strewn-field covering an area of several hundred square kilometers (Bourbot-Denise et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It seems a more exciting task to increase the number of known falls, rather than decreasing it, following the example of Bourot-Denise et al (1998) for Gao and Guenie falls from Burkina Faso. However, reducing the number of errors in the catalogue is also a positive contribution to the reliability ofthe meteorite database.…”
Section: Discussionmentioning
confidence: 99%